Vegetação, Paisagem e o Planejamento do Uso da Terra (GEOgraphia, 2009)
Resumo O levantamento e mapeamento da vegetação vem tendo uma importância crescente no plane-jamento do uso da terra em regiões florestais tropicais. Os mapas de vegetação podem ser utilizados indi-vidualmente ou de forma integrada com outros mapas temáticos, para a caracterização e análise da paisa-gem, a qual serve de orientação no processo de planejamento do uso da terra. O uso de mapas ecológicos ou da paisagem contendo informações combinadas de diferentes atributos da paisagem, é um avanço sig-nificativo na avaliação das terras. O enfoque holístico possibilita uma melhor compreensão das inter-rela-ções entre a vegetação e os outros atributos, melhorando significativamente as análises e avaliações resul-tantes . O enfoque paisagístico pode auxiliar ainda no próprio levantamento da vegetação, como o mapea-mento dos diversos tipos de comunidades ou formações florestais de acordo com as características domi-nantes da ambiente físico, como o relevo. Sistemas de Informações Geográficas (SIG) vêm sendo cada vez mais utilizados como banco de dados ambientais, onde dados relevantes podem ser armazenados, manipu-lados, atualizados e combinados em diversas análises e avaliações de diferentes cenários de evolução dinâ-mica natural e antrópica da paisagem florestal tropical. Palavras-Chave: Planejamento do Uso da Terra, Floresta Tropical, Análise da Paisagem, SIG.Abstract The vegetation survey and mapping has an increasingly important role in the land use planning in tropical forest regions. Vegetation maps can be used individually or integrated with other the-matic maps for the characterisation and analysis of the landscape, which will direct the land use planning process. The use of landscape ecological maps, which combine information from different land attributes is a significant advance on land evaluation and appraisal. The holistic approach allows a better understan-ding of the relationships between vegetation and other land attributes, which can improve considerably the results of the analyses and evaluation. The landscape approach can also improve the vegetation or forest survey, helping to map the different forest types according to the dominant aspects of the physical environment, such as relief. Geographical information systems (GIS) are increasingly used as a spatial environmental data base, where relevant data can be stored, handled, updated and combined in the analy-sis and evaluation of alternative scenarios of the natural and anthropogenic tropical forest landscape dynamics. Keywords: Land Use Planning, Tropical Forest, Landscape Analysis, GIS.The vegetation survey and mapping has an increasingly important role in the land use planning in tropical forest regions. Vegetation maps can be used individually or integrated with other the-matic maps for the characterisation and analysis of the landscape, which will direct the land use planning process. The use of landscape ecological maps, which combine information from different land attributes is a significant advance on land evaluation and appraisal. The holistic approach allows a better understan-ding of the relationships between vegetation and other land attributes, which can improve considerably the results of the analyses and evaluation. The landscape approach can also improve the vegetation or forest survey, helping to map the different forest types according to the dominant aspects of the physical environment, such as relief. Geographical information systems (GIS) are increasingly used as a spatial environmental data base, where relevant data can be stored, handled, updated and combined in the analy-sis and evaluation of alternative scenarios of the natural and anthropogenic tropical forest landscape dynamics. Keywords: Land Use Planning, Tropical Forest, Landscape Analysis, GIS.